2020
DOI: 10.1002/adma.202002404
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose in Emulsions and Heterogeneous Water‐Based Polymer Systems: A Review

Abstract: With trends in recent literature and industrial research shifting toward sustainable and renewable materials, cellulose shows much promise as an alternative to petroleum-derived chemicals. Cellulose is the most abundant natural polymer, with annual production estimated to be over 10 11 tons. [1] Cellulose is widely distributed in higher plants, in several marine animals (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(121 citation statements)
references
References 303 publications
(452 reference statements)
0
120
0
1
Order By: Relevance
“…[ 11 ] This has led to the incorporation of CNCs in water‐based heterogenous polymerizations such as dispersion, suspension, and emulsion polymerizations. [ 12 ] As noted earlier, emulsion polymerization aligns with “green” production methods due to the omission of organic solvents, and therefore a reduction in air‐released volatile organic compounds. [ 13 ] The well‐established fundamentals of emulsion polymerization have endowed researchers with an industrially relevant platform which has been exploited to produce a variety of products such as plastics, coatings, rubbers, and adhesives.…”
Section: Figurementioning
confidence: 97%
See 2 more Smart Citations
“…[ 11 ] This has led to the incorporation of CNCs in water‐based heterogenous polymerizations such as dispersion, suspension, and emulsion polymerizations. [ 12 ] As noted earlier, emulsion polymerization aligns with “green” production methods due to the omission of organic solvents, and therefore a reduction in air‐released volatile organic compounds. [ 13 ] The well‐established fundamentals of emulsion polymerization have endowed researchers with an industrially relevant platform which has been exploited to produce a variety of products such as plastics, coatings, rubbers, and adhesives.…”
Section: Figurementioning
confidence: 97%
“…The combined use of CNCs and emulsion polymerization improves the sustainability of polymer nanocomposites along with their mechanical, rheological, thermal, and barrier properties. [ 12 ] Favier et al. [ 17 ] were pioneers in blending various concentrations of CNCs with soft polymer latexes in suspension.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, their decreased environmental burden, the wide selection of potential raw materials and better control over the final products have resulted in increased research interest in developing high-performance, latex-based PSAs [3]. Recent work, for example, has shown that the addition of cellulose nanocrystals (CNCs) to emulsion polymerized acrylic PSAs simultaneously improves all three adhesive metrics (tack, peel strength and shear strength) [4][5][6][7][8][9]; an unusual trend in PSA properties where an increase in shear strength often corresponds to a decrease in tack and peel strength, or vice versa [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocelluloses can also adsorb at latex particle surfaces or reinforce dried latex films used, for example, as coatings and adhesives Dastjerdi et al, 2017aDastjerdi et al, , 2017bDastjerdi et al, , 2018Dastjerdi et al, , 2019Ouzas et al, 2018Ouzas et al, , 2019Pakdel et al, 2020). However, as these structures are outside of the scope of this review, the reader is referred to a comprehensive review on the subject by Kedzior et al, 2020.…”
Section: Nanocellulose Capsulesmentioning
confidence: 99%